Effect of ultrasonic treatment combined with 1‐methylcyclopropene (1‐MCP) on storage quality and ethylene receptors gene expression in harvested apple fruit. Issue 8 (30th June 2019) - Xu, Fangxu; Liu, Shiyang; Xiao, Zhigang; Fu, Liang
Abstract: The objective of our study was to investigate the effectiveness of ultrasonic treatment combined with 1‐methylcyclopropene (1‐MCP) on storage quality and gene expression of postharvest apples compared with ultrasonic or 1‐MCP treatment alone. Ethylene production, respiratory rate, firmness, soluble solid content (SSC), peroxidase (POD), superoxide dismutase (SOD), catalase (CAT) activity, and ethylene receptors gene expression of apples were tested. The results indicated 1‐MCP or ultrasonic treatment‐restrained ethylene production and respiratory rate, improved firmness, suppressed the escalation of SSC, enhanced the activities of POD, SOD, and CAT, suppressed the gene expression level of MdETR1 and MdERS1 compared with the untreated samples. Furthermore, effect of the combination was more observable than that of ultrasonic or 1‐MCP alone. In a word, the results proved the technology of ultrasonic plus 1‐MCP was effective to enhance the storage quality and lengthen the life span of apples. Practical applications: Jonah king apple has the characteristics of crisp texture, long shelf life, high sugar content, and solidity‐acid ratio, which is suitable for the taste of east and southeast Asian. However, as for a kind of respiration climacteric fruit, the commercial quality of Jonah king apple dramatically drops during the later stage of storage due to its softening, superficial scald, and perishability. One of the primary problems in apple preservation is the reduction of microbial growth, which directly affects the internal quality of apple fruit. The aim of present work is to estimate the effect of ultrasonic plus 1‐MCP treatment on storage quality and life span of apple fruit, as well as to provide theoretical basis to enhance the storage quality and lengthen the life span of apples.